2021
DOI: 10.3390/ijerph18094636
|View full text |Cite
|
Sign up to set email alerts
|

Disability-Free Life Expectancy among People Over 60 Years Old by Sex, Urban and Rural Areas in Jiangxi Province, China

Abstract: Objective: To estimate and compare age trends and the disability-free life expectancy (DFLE) of the population over 60 years old in 2018 in Jiangxi Province, China, by sex and urban–rural areas. Methods: The model life table was employed to estimate the age-specific mortality rate by sex and urban–rural areas, based on the Summary of Health Statistics of Jiangxi Province in 2018 and the Sixth National Health Service survey of Jiangxi Province. DFLE and its ratio to life expectancy (LE) were obtained by the Sul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 36 publications
0
3
2
Order By: Relevance
“…In 2001, the WHO published the International Classification of Functioning, Disability and Health, and scholars from various countries began to use disability or function as a health indicator to measure the healthy life expectancy of older adult. Wang et al (25) estimated the healthy life expectancy of older adult aged 60 and older in Jiangxi Province, China, in 2018, and the results showed that the disability-free healthy life expectancy of older adult aged 60 was 18.12 more years, which was significantly higher than the results of this study. Disability-free healthy life expectancy evaluates the health status of a population by combining the disability status of a population with life expectancy.…”
Section: Discussioncontrasting
confidence: 73%
“…In 2001, the WHO published the International Classification of Functioning, Disability and Health, and scholars from various countries began to use disability or function as a health indicator to measure the healthy life expectancy of older adult. Wang et al (25) estimated the healthy life expectancy of older adult aged 60 and older in Jiangxi Province, China, in 2018, and the results showed that the disability-free healthy life expectancy of older adult aged 60 was 18.12 more years, which was significantly higher than the results of this study. Disability-free healthy life expectancy evaluates the health status of a population by combining the disability status of a population with life expectancy.…”
Section: Discussioncontrasting
confidence: 73%
“…In 2001, the WHO published the International Classi cation of Functioning, Disability and Health, and scholars from various countries began to use disability or function as a health indicator to measure the healthy life expectancy of elderly individuals. Wang et al [24] estimated the healthy life expectancy of elderly individuals aged 60 and older in Jiangxi Province, China, in 2018, and the results showed that the disability-free healthy life expectancy of elderly individuals aged 60 was 18.12 more years, which was signi cantly higher than the results of this study. Disability-free healthy life expectancy evaluates the health status of a population by combining the disability status of a population with life expectancy.…”
Section: Discussioncontrasting
confidence: 70%
“…The diagnoses were based on the International Classification of Diseases (ICD)-10 codes and Chinese names of medical diseases. We included all patients aged >60 years without other inclusion and exclusion criteria (19). The patients were divided into groups according to sex (male and female) and age (≤74 years, "younger older" persons; 75-89 years, "senior older" persons; ≥90 years, "older persons with longevity") (17,20).…”
Section: Methodsmentioning
confidence: 99%